Oplyst sundhedspolitik? Overdødelighed hos plejebørn fra opfostringsstiftelsen 1770-1800 - Schultz, Annette Østergaard (Historisk Tidsskrift, 2022)
Enlightened Health Politics? Infant Mortality among Foster Children Handled by Opfostringsstiftelsen 1770–1800 From 1750, unwed mothers in Copenhagen could give birth anonymously and without charge at Fødselsstiftelsen. In most instances, the children were raised by foster parents, mostly artisans, in Copenhagen. However, infant mortality was high, averaging 70 per cent. In 1770, aided by the enlightened politics of the royal favourite Johann Friedrich Struensee and based on mercantilist and cameralist principles, the Opfostringsstiftelsen, a foundling office, was established. During the next 30 years, Opfostringsstiftelsen systematically distributed abandoned children, approximately 10,000 in all, to foster parents throughout Zealand in order to raise survival rates and stimulate population growth and wealth. Nevertheless, the state accepted a very high mortality among foster children. Average mortality among children in the countryside aged 0–9 years was 30 per cent, but nearly 70 per cent among foster children. Between 500 and 1000 children were born each year, 1775-1800, at Fødselsstiftelsen. Between five and eight per cent were stillborn and 3-20 per cent of the live-born died during their first week at the institution. Most of the infants were registered as “Kassebarn” (box baby), which meant that the infant was eligible for transfer to a foster family in Zealand. Many low-income farmers in Zealand wanted a foster child (and an extra income), but from 1789 it became more difficult for Opfostringsstiftelsen to recruit foster families there, due to effects of agricultural reform. As a result transfers were delayed and more children died before a foster family could be found. From 1790, Opfostringsstiftelsen resorted to interim foster care in Copenhagen. Only a small part of the difference in infant mortality in general and infant mortality among the foster children may be explained by the fact that foster children were not breastfed. Another explanation is the stipulation by law that a foster family would be offered another child if the first one died. One could venture, then, that the law favoured foster parents who were less than adequate in fulfilling their duty. Indeed, a few pairs of foster parents received several children who all died. However, most of the foster parents only had a single child, or two. It is difficult to find clear patterns in mortality among foster children. Much depended on the local vicar, who had to certify the suitability of the foster parents. How to reduce the mortality was a question never asked. It was a basic condition that children died. Every single child who survived was a godsend.